The Russo-Ukrainian War : the return of history - Plokhy, Serhii (Penguin Books, 2023)
"An authoritative history of Europe's largest military conflict since World War II, from the New York Times best-selling author of The Gates of Europe. Despite repeated warnings from the White House, Russia's invasion of Ukraine in February 2022 shocked the world. Why did Putin start the war-and why has it unfolded in previously unimaginable ways? Ukrainians have resisted a superior military; the West has united, while Russia grows increasingly isolated. Serhii Plokhy, a leading historian of Ukraine and the Cold War, offers a definitive account of this conflict, its origins, course, and the already apparent and possible future consequences. Though the current war began eight years before the all-out assault-on February 27, 2014, when Russian armed forces seized the building of the Crimean parliament--the roots of this conflict can be traced back even earlier, to post-Soviet tensions and imperial collapse in the nineteenth and twentieth centuries. Providing a broad historical context and an examination of Ukraine and Russia's ideas and cultures, as well as domestic and international politics, Plokhy reveals that while this new Cold War was not inevitable, it was predictable. Ukraine, Plokhy argues, has remained central to Russia's idea of itself even as Ukrainians have followed a radically different path. In a new international environment defined by the proliferation of nuclear weapons, the disintegration of the post-Cold War international order, and a resurgence of populist nationalism, Ukraine is now more than ever the most volatile fault line between authoritarianism and democratic Europe"--
Includes bibliographical references and index.
Keywords: Russo-Ukrainian War, 2014- -- Causes; Russian Invasion of Ukraine, 2022.; Ukraine -- Politics and government -- 2014-; Russia (Federation) -- Politics and government -- 1991-